(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The combination of Perindopril (PRN) and Losartan (LRN) is used in the management of hypertension. The present work was focused on the development of RP-HPLC method for the estimation of perindopril and losartan in binary mixtures. The separation was performed on LUNA C18 column at 210 nm by isocratic elution. Methanol and phosphate buffer (pH 6.8) in the ratio of 85:15 with a flow rate of 0.8 ml/min at ambient temperature was found to be suitable for chromatographic separation. Perindopril and losartan exhibits linearity in the ranges of 200-500 and 30-80 µg/mL respectively. The proposed method evidenced the absence of chromatographic interference by pharmaceutical excipients. Separation of the mixtures was proved to be good from the resolution of the peaks. Validation and recovery studies were performed and the results proved the method to be suitable for routine analysis.